Pemutihan pulp ampas tebu untuk bahan dasar pembuatan CMC=Bleaching of bagasse pulp for the raw material of CMC - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT The Carboxy Methyl Cellulose (CMC) had been made from bleached bagasse pulp. This research was conducted to know the bleaching methode using various concentration of hypoclorite and peracetic acid viewed from their physical and chemical properties and to observed the effect of Na-monocloroacetate concentration and aging duration on degree of substitution, purity and viscocity of the CMC. The bleaching process was carried out using hypoclorite at 0, 2,5, 5, 7,5 and 10% at temperature of 40Â°C for 3 hours and peracetic acid a.tO, 1,2, 4,6, 8,10,12,14 and 16% at 85Â°C for 3 hours. After works, the pulp was washed and dried at room temperature, analyzed for brightness, yield, cellulose, hemicellulose, lignin, dissolved material, ash content and the value of water retention. The best result of bleaching was used as raw material of the CMC. The CMC was made using concentration difference of Na-monocloro-acetat. The steps included alkalization, carboxymethylation, aging, neutralization, screening and drying at room temperature. The CMC was analyzed for degree of substitution, purity and viscocity. The result showed that higher hypoclorite concentration increased in brighteness and content of dissolved material and decreased in cellulose, hemicellulose, lignin, ash and yield. The increase of peracetic to the level of 6% 1 increased yield and cellulose. Whereas the increased above 6% decreased in yield, brighteness, cellulose, hemicellulose, lignin and ash, but it increased content of dissolved material and water retention value. The best result was obtained at the concentration of 6% with the yield of 96%, brighteness 93, content of cellulose, hemicellulose, lignin, ash and water retention value of 70,16%, 18,22%, 9,236%, 1,56% and 6,62, respectively. The increased in monocloroacetate decreased the substitution degree at NaOH supplementation of 62 gram/100 gram pulp with 82 ml of water and increased the purity degree and viscocity of the CMC The aging of 7 days and 14 days didn't result in the difference in viscosity of the CMC. The increased in substitution degree above 1,2 decreased the viscocity CMC 1%.